Role of Surgery in Clostridium difficile Infection - Vely, Aela; Ferrada, Paula (Clinics in Colon and Rectal Surgery, 2020)
Clostridium (reclassified as “Clostridioides”) difficile infection (CDI) occurs as a chronic or an acute illness with intensity varying from mild to severe. Although most cases of CDI can be managed with antibiotics and supportive care, when the patient presents with fulminant disease, the early decision to perform surgery is imperative for survival. The current standard of care is the subtotal colectomy. However, loop ileostomy with vancomycin enemas delivered into the colonic mucosa has been described as a viable option on selected patients.
Keywords: Clostridium difficile infection; surgery for complicated Clostridium difficile infection subtotal colectomy; loop ileostomy for complicated Clostridium difficile infection